1027. Earlier Is Better: Progress Toward Decreased Time to Optimal Therapy and Improved Antibiotic Stewardship for Gram-positive Bloodstream Infections Through Use of GenMark Dx ePlex system. (4th December 2021) - White, Cameron; Meeder, Jeremy; Moates, Derek; Pierce, Hannah; McCarty, Todd P; Lee, Rachael A; Leal, Sixto M
Abstract: Background: The ePlex BCID Gram-Positive (GP) panel utilizes electrowetting technology to detect the most common causes of GP bacteremia (20 targets) and 4 antimicrobial resistance (AMR) genes in positive blood culture (BC) bottles. Rapid detection of intrinsic vancomycin resistance and acquired resistance genes ( mecA, mecC, vanA, vanB ) enables early optimization of antimicrobial therapy whereas early detection of common contaminants is expected to decrease unnecessary antibiotic utilization and hospitalizations. Methods: In this prospective study, aliquots of BC bottles with GP bacteria detected on Gram stain (GS) (n=101) received standard of care (SOC) culture and antimicrobial susceptibility testing (AST). Additionally, samples were evaluated with the BCID-GP panel but only SOC results were reported in the EMR and available to inform clinical decisions. Patients were excluded if the sample was a subsequent culture in a persistent episode of bacteremia (n=17) or if the assay failed (n=4). Chart review was performed to evaluate the expected impact of the BCID-GP panel on the time to organism identification, AST results, and optimization of antimicrobial therapy. Results: A total of 80 patients were included in the final analysis (Table 1). S. epidermidis was the most common bacteria identified, followed by S. aureus, and other coagulase-negative staphylococci. Thirty-nine patients with staphylococci (48.8%) had the mecA gene detected and 2 patients with E. faecium had the vanA gene detected. The BCID-GP panel saved a mean of 24.4 hours (h) to identification and 48.3h to susceptibility testing compared to standard methods across all patients. In 38 patients (47.5%), the BCID-GP panel result could have enabled an earlier change in antibiotic therapy. Table 2 highlights opportunities to optimize antimicrobial therapy 53.4h earlier for 16 (20%) patients with organisms expressing AMR genes, 29.2h earlier for 8 (10%) patients infected with organisms, such as streptococci, with very low resistance rates, and to stop antimicrobial therapy 42.9h earlier for 14 (17.5%) patients with contaminated blood cultures. Conclusion: The BCID-GP panel could have enabled earlier optimization or stopping of antibiotics in many patients with significant time savings compared to standard laboratory methods. Disclosures: Todd P. McCarty, MD, Cidara (Grant/Research Support)GenMark (Grant/Research Support, Other Financial or Material Support, Honoraria for Research Presentation)T2 Biosystems (Consultant) Sixto M. Leal, Jr., MD, PhD, Abnova (Grant/Research Support)AltImmune (Grant/Research Support)Amplyx Pharmaceuticals (Grant/Research Support)Astellas Pharmaceuticals (Grant/Research Support)CNINE Dx (Grant/Research Support)GenMark Diagnostics (Grant/Research Support, Other Financial or Material Support, Honoraria- Research Presentation)IHMA (Grant/Research Support)IMMY Dx (Grant/Research Support)JMI/Sentry (Grant/Research Support)mFluiDx Dx (Grant/Research Support)SpeeDx Dx (Grant/Research Support)Tetraphase Pharmaceuticals (Grant/Research Support)